A Novel in vitro Model Delineating Hair Cell Regeneration and Neural Reinnervation in Adult Mouse Cochlea - Li, Wenyan; Quan, Yizhou; Huang, Mingqian; Wei, Wei; Shu, Yilai; Li, Huawei; Chen, Zheng-Yi (Frontiers in Molecular Neuroscience, 2022)
Study of adult mammalian auditory system such as regeneration has been hampered by the lack of an in vitro system in which hypotheses can be tested efficiently. This is primarily due to the fact that the adult inner ear is encased in the toughest bone of the body whereas its removal leads to death of the sensory epithelium in culture. We hypothesized that we could take advantage of the elaborated cochlear structure to maintain the overall inner ear architecture and improve sensory epithelium survival in culture. We show that by culturing adult mouse cochlea with the intact bone the sensory epithelial cells survive long-term in culture condition with a well-preserved structure. To evaluate the utility of the explant culture system, we demonstrate that overexpression of Atoh1, a hair cell fate determining factor, is sufficient to induce transdifferentiation of adult supporting cells to hair cell-like cells (HCLCs). Transdifferentiation-derived HCLCs resemble developmentally young hair cells and are able to attract adult ganglion neurites. Further, using a damage model, we show that degenerated adult ganglions respond to regenerated HCLCs by directional neurite outgrowth that leads to HCLC-neuron contacts, strongly supporting the intrinsic properties of the HCLCs in establishing HCLC-neuron connections. The whole adult cochlea explant culture is suitable for diverse studies of the adult inner ear including regeneration, hair cell-neuron pathways and inner ear drug screening.